Pathology of Lung Disease c y Helmut Popper. - Popper, Helmut; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This well-illustrated textbook covers the full range of lung and pleural diseases from the pathologic standpoint. Both diseases of adults and pediatric lung diseases are presented. The book will serve as an excellent guide to the diagnosis of these diseases, but in addition it explains the disease mechanisms and etiology. Genetics and molecular biology are also discussed whenever necessary for a full understanding. The author is an internationally recognized expert who runs courses on lung and pleural pathology attended by participants from all over the world. In compiling this book, he has drawn on more than 30 years$1 (Bexperience in the field.s
Development of the lung -- Anatomy and Histology of normal lung -- Pediatric Pulmonary Pathology -- Edema -- Air filling diseases -- Airway diseases -- Smoking related lung diseases.
Keywords: Medicine; Molecular biology; Infectious diseases; Respiratory organs -- Diseases; Oncology; Pathology; Medicine & Public Health; Pathology; Pneumology/Respiratory System; Molecular Medicine; Infectious diseases; Oncology